Morphological variations of mandibular first premolar in a Saudi Arabian subpopulation evaluated using Cone Beam Computed Tomography CBCT - Youssef A. Algarni; Muna J. Almufarrij; Ibrahim A. Almoshafi; Haneen H. Alhayaza; Nuha Alghamdi; Suheel Manzoor Baba (Elsevier, 2019)
In-depth knowledge of common and aberrant pulp morphology is essential for appropriate diagnosis and treatment planning prior to commencing root canal treatment. Radicular morphology of mandibular premolars has been extensively studied. Considerable variation in the number of canals and roots found in these teeth has been reported. Aim: The purpose of this study is to investigate the root and root canal morphology of mandibular first premolar among Saudi Arabian subpopulation in Aseer using CBCT. Methods: Cone-beam computed tomography images of Mandibular first premolar were taken from 166 patients which were referred to Armed Forces Hospitals Southern Region (AFHSR), Khamis Mushayt, Asir region Saudi Arabia. All the images were assessed by two Evaluators (An Endodontist and a Radiologist). Inter-examiner reliability was determined and was assessed by KAPPA value. Results: Gender and bilateral distribution differences were calculated and were determined using the Chi-Squared test (χ2-test). Differences were considered significant when P > 0.05 using SPSS Statistics software (ver. 22.0; SPSS, Inc., Chicago, IL, USA). Results: The mandibular first premolar (n = 216) distributed as 120 teeth in female and 96 teeth in male. Out of the 120 teeth examined in female groups one canal was seen in 95 teeth, two canals in 19 teeth and three canals in 6 teeth where as in the Male group out of 96 teeth, 53 teeth showed one canal, 33 teeth with two canals whereas 12 teeth showed presence of three canals. Conclusion: Endodontic therapy of mandibular premolars is a challenge for clinician because of their frequent morphological and anatomical abnormalities. Proper knowledge about number of root canals and canal configuration is a key to success in Endodontic. There is a great variability in different population regarding the root canal configuration in mandibular pre-molars. However most studies state the mandibular first premolar has one root canal. Also the most prevalent type of root canal found was Type I vertucci.